Pengaruh Frekuensi dan Periode Pemberian Pakan yang Berbeda terhadap Tingkah Laku Makan Burung Puyuh Petelur - H. R. Tamba; E. Suprijatna; U. Atmomarsono (Universitas Bengkulu, 2019)
Research aims to evaluate the influence of the frequency and period of the different feed to conduct quail laying on environmental conditions temperaturnya fluctuate tropical.The research uses 180 tail quail female age 21 days randomly placed in a cage battery.Any unit experiment consisting of 5 tail.The research uses commercial feed b11 in the period grower and b82 p in the period layer.The treatment was conducted over 9 sunday that begins at the age of 5 sunday reached the age of 13 weeks.The research uses random design complete ( ral ) pattern factorials with 2 factors, the frequency of (A) and A1 (1 time), A2 (2 times) and A3 (3 times) and period (B) to B1 (5:00 to 21:00 pm) , B2 (07:00 to 21:00 GMT) and B3 (09:00 to 21:00 GMT). The parameters observed were the behavior of feeding, drinking, walking and resting. The data were analyzed variance with F test at 5% level and continued Duncan Double Area Test. The results showed that frequency and feeding period did not show significant interaction with eating behavior, drinking walking and rest, but feeding frequency was 1 times significantly (P <0,05) to feeding behavior at the beginning of production. It was concluded that when viewed from the eating behavior, the combination of frequency treatment 1 times with a period of administration of 14 hours (A1B2) showed more quail feeding activity.Keywords: feeding frequency, period of feeding, behavior, quail laying.